2016
DOI: 10.14393/bj-v32n4a2016-30214
|View full text |Cite
|
Sign up to set email alerts
|

Repeatability of biometric characteristics of Juçara palm fruit

Abstract: Juçara is a plant that occurs in the Brazilian Atlantic Forest which presents high ecological importance to the biodiversity and is present on the list of endangered species. The fruits are known as super fruits because they present chemical characteristics of great importance. Due to its elevated economic importance and for the low number of researches with this species, the first step is to make the pre-breeding of the species. This consists in morphological characterization, which is very dependent on time … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…To evaluate the equatorial and longitudinal diameters of fruits and seeds (EDF, LDF, EDS and LDS, respectively) (mm), five fruits were measured in millimeters (mm) using a digital caliper. Marçal et al (2016) 31 concluded that five measurements are necessary to achieve a 95% coefficient of determination — although they provide additional information on the studies, measurements beyond this number increase cost and evaluation time.…”
Section: Methodsmentioning
confidence: 99%
“…To evaluate the equatorial and longitudinal diameters of fruits and seeds (EDF, LDF, EDS and LDS, respectively) (mm), five fruits were measured in millimeters (mm) using a digital caliper. Marçal et al (2016) 31 concluded that five measurements are necessary to achieve a 95% coefficient of determination — although they provide additional information on the studies, measurements beyond this number increase cost and evaluation time.…”
Section: Methodsmentioning
confidence: 99%
“…By this estimate, it is possible to forecast how many evaluations will be needed for selection with greater reliability. Thus, estimated heritability, individual repeatability, and genotypic correlation parameters are essential during harvests for the breeder to select superior individuals (MARÇAL et al, 2016). In some studies, with perennial crops in this scenario, the authors found that to select promising genotypes with greater efficiency, it is more convenient to increase the number of years and places evaluated than the number of progenies (DANNER et al, 2010;BRUNA et al, 2012;CARGNIN, 2016;IMAI et al, 2016;RODRIGUES et al, 2017;QUINTAL et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The REML/BLUP methodology also allows estimating the repeatability coefficient, which is highly relevant, considering that selection in perennial species requires a long time due to the long productive and reproductive cycles and the need to conduct extensive and expensive experiments. The REML/BLUP allows selecting superior genotypes with greater efficiency and lower operating costs (Marçal et al, 2016).…”
Section: Introductionmentioning
confidence: 99%